Measuring the effectiveness of programmed instructions (PI) to learn design thinking concepts for secondary school students - Apoorv Naresh Bhatt; Amaresh Chakrabarti (Design Science)
Self-instructional media in education has the potential to address educational challenges such as accessibility, flexible and personalised learning, real-time assessment and resource efficiency. The objectives of this study are to (1) develop programmed instructions to teach design thinking concepts and (2) investigate its effects on secondary school students’ understanding of these concepts. A design thinking workshop was conducted with secondary school students; subsequently, their understanding of design thinking concepts gained through digital programmed instructions was evaluated. The study involved 33 novice secondary school students from grades 6 to 9 in India, who worked in teams to find and solve real-life, open-ended, complex problems during the workshop using the design thinking process. Data on (i) the individual performance in understanding design thinking concepts and (ii) team performance in design problem finding and solving were collected using individual tests and teams’ outcome evaluations, respectively. Students’ perceptions of the effectiveness of the programmed instructions for supporting understanding of the concepts were also captured. Results show the positive effects on students’ understanding of design thinking concepts as well as on their problem-finding and solving skills. The results justify the use of programmed instructions in secondary school curricula to advance design thinking concepts. The current version of programmed instruction has limitations, including the absence of branching mechanisms, a detailed feedback system, multimodal content and backend functionalities. Future work will aim to address these issues and overcome these shortcomings.